The Impact of Health Education on Parental Knowledge in Preventing Tuberculosis in Children - Widiawati, Susi; Khairani, Annisa (Universitas Padjadjaran, 2025)
Tuberculosis (TB) is an infectious disease that causes the second-largest number of deaths after Covid-19. There were 1,627 cases of TB in children in Jambi Province in 2021, while in the city of Jambi, the highest number of cases were in the Puskesmas Familiar Besar area with 159 cases. The impact of TB disease on children will disrupt growth and development. There is a need to address the impacts and new cases of TB in various ways, including health education for children's parents. This study aims to determine the effect of health education on parents' knowledge in preventing tuberculosis in children. This research is quantitative research with a pre-experimental design. The research subjects were parents who had children With a sample of 34 people, the sample was taken using a purposive sampling technique. Data were collected from 5 to 24 June 2023. The intervention provided was TB prevention material with video tools and leaflets. Data was collected using a questionnaire and analyzed univariately and bivariately using the T-Test. The results of univariate analysis showed that the average value of maternal knowledge before the intervention was 6.38 and the average value of maternal knowledge after the intervention was 8.15. The results of the bivariate analysis showed the influence of health education on parental knowledge in preventing tuberculosis in children with a p-value of 0.001. It is hoped that Puskesmas officers will provide health education in various activities to prevent the transmission of tuberculosis to children. This research can be developed with a digital education application to prevent TB in children.